Physical-hydric quality of oxisol under irrigation and brachiaria in farming od coffee inthe cerrado region - Rocha, Omar Cruz; Guerra, Antonio Fernando; Ramos, Maria Lucrécia Gerosa; Oliveira, Alberto da Silva; Bartholo, Gabriel Ferreira (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to evaluate the effect of irrigation and cultivation of brachiaria among coffee trees lines on physical-hydric Oxisol quality at Brazilian central plateau. The experiment was carried out in five randomized blocks in a factorial design 2 x 2, with two water treatments, irrigated and rainfed systems, and two management systems, with and without brachiaria between coffee trees lines. The research strategy was based on studying soil water storage based on porosity distribution due to the behavior of physical parameters in different water and management treatments. Soil samples were collected in duplicate in each plot at depths from 0.0 to 0.05, 0.05 to 0.10, 0.10 and 0.20 m. The irrigation regime increased soil bulk density in the surface layer without reducing its readily available water that, due to presence of brachiaria was increased by 18%. In general, irrigated brachiaria had a positive effect on the physical-hydric soil characteristics of the soil and promoted an increase in readly available soil microporosity from the redistribution of pore diameter characterized by increasing retention curve amplitude in the soil water tension range corresponding to the readily-available water.